2011
DOI: 10.1021/jp2071327
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the Adsorption of Nitrogen and Sulfur Atoms on Gold (111), (100), and (211) Surfaces

Abstract: Nitrogen and sulfur atom adsorption on flat and stepped gold surfaces are examined by density functional theory. With detailed investigation of adatom location on the (111), (100), and (211) gold surfaces, nitrogen and sulfur atom adsorption are compared with reference to previous work on the oxygen/gold system. Sulfur adsorbed most strongly, followed by oxygen and nitrogen. The results demonstrate the preference for 3-fold over 2-fold and single-fold adatom coordination as well as the role of low coordinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…At low and intermediate coverage (lower than 0.33 ML) it is well established by DFT calculations 16,[31][32][33] that sulfur atoms occupy threefold positions on the Au(111) surfaces. In these conditions, they stay on the surface as monoatomic species due to the considerable distance that separates two neighboring sulfur atoms (at least more than twice the sulfursulfur bond distance).…”
Section: Dft Resultsmentioning
confidence: 95%
“…At low and intermediate coverage (lower than 0.33 ML) it is well established by DFT calculations 16,[31][32][33] that sulfur atoms occupy threefold positions on the Au(111) surfaces. In these conditions, they stay on the surface as monoatomic species due to the considerable distance that separates two neighboring sulfur atoms (at least more than twice the sulfursulfur bond distance).…”
Section: Dft Resultsmentioning
confidence: 95%
“…Previous studies normally report the preferred sulfur adsorption binding site, the binding (adsorption) energy, the sulfur-surface interatomic distances, and the diffusion energy of sulfur. The preferred adsorption site and the binding energy have been reported for sulfur on Ni(111), 3,9,17,28,30,31 Cu(111), 9,[13][14][15]17,25,26,31,35 Rh(111), 17 Pd(111), 4,15,22,26,35 Ag(111), 2,15,17,25,35 Ir(111), 34 Pt(111), 4,17,37 Au(111), 15,16,22,26 Ni(110), 9 Cu(110), 5,9,13 Au(110), 21 Ni(100), 9,12,30 Cu(100), 9,12,14 Ir(100), 29 Au(100), 7,16 Pd(211), 36 and Au(211). 16 Th...…”
Section: Introductionmentioning
confidence: 96%
“…Density Functional Theory (DFT) calculations have been performed to study the adsorption of sulfur on the low-index surfaces of multiple Face Center Cubic (FCC) metals. [3][4][5]7,9,10,[12][13][14][15][16][17]21,22,25,26,[28][29][30][33][34][35][36][37] We surveyed the DFT calculations of sulfur on FCC metal surfaces reported since the year 2000; see Ref. 39 for an account of earlier calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ampicillin was the first of a number of so-called broad spectrum penicillins and is equivalent to amoxicillin in terms of spectrum and level of activity. DFT studies have evaluated the ability of the free S, O and N atoms to bind to gold surfaces and have concluded that the adsorption energies follow the order S > O > N. 58 From an experimental point of view, no anchorage point has been clearly identified in the literature. 8 The modelling of these nanoconjugates, i.e.…”
Section: The Gold-ampicillin Interfacementioning
confidence: 99%